PENGELOLAAN FASILITAS AIR SIDE BANDARA INTERNASIONAL AHMAD YANI SEMARANG - , HENRI RIYANTI; , Devi Oktaviana Latif, ST. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia is a country that has many islands. The distance between the islands to one another not merely accessible by land transport. Coupled with the rapid mobility, it must be balanced with the development of transport facilities. Public transport requires a fast, convenient, and inexpensive. Therefore, people begin to rely on air transport. PT. Angkasa Pura I (Persero) Ahmad Yani International Airport in Semarang as one of the leading providers of air transport services which provide optimal facilities for the community. So that the necessary of the existing facilities at Ahmad Yani International Airport in Semarang. In the job training authors directly involved in the work handled by the Engineering Department of General Ahmad Yani International Airport in Semarang, in particular the work on the airport side of water facilities. So authors can find out in particular the management air fasilities of Ahmad Yani International Airport in Semarang. Activities of management air side facilities management is divided into 2 (two) types of activities, namely an airport engineering and airport operations.